THE ANALYSIS OF INTERPERSONAL MEANING (MOOD), IDEATIONAL MEANING (TRANSITIVITY) AND TEXTUAL MEANING (THEME) OF NEWS ITEM TEXT ENTITLED â€œNIKITA MIRZANI: I`M NOT A PROSTITUTEâ€ - Prawiro, Indra Yoga (Wiralodra English Journal, 2017)
Today, media has become primary needs as food and clothing. It has played significant role in strengthening the society that is as a "mirror" of the modern society. It?s used not only to inform people about current, new affairs and what is happening around them and the world but also to form opinions and make judgments regarding various issues. Cohen, (1963); McCombs & Shaw, (1972) stated that when mass media emphasize a topic, the audience/public receiving the message will consider this topic to be important. However, systemic functional grammar is concerned primarily with the grammar choices makes available to speakers and writers. These choices relate speakers' and writers' intentions to the concrete forms of a language. This study is attempt to investigate the interpersonal meaning (mood), ideational meaning (transitivity) and textual meaning (theme) of news item text entitled ?Nikita Mirzani: I`m Not a Prostitute?.The news becomes very interesting for some people, because this news is indicated as distractor issue for Freeport cases.After analyzing the mood system in this text, so the writer can conclude that all of the information in this news is declarative mood. For example when the Nikita stated you can confront me with O and F (pimp suspects). I do not know them. This proof gives us justification that the speakers indeed intentionally give fruitful and clear information to each other. The use of full declaratives here also indicates that the text shares a common focus on the giving of information. There is only full declarative in this text, there is no full polar interrogative, full WH-interrogative, imperative and so on. After we discuss the mood types, and then move on the next table, about Modality and Polarity. There are four modality used in this text. Those are the use of can (two times), could and might. So, it assumes that some information given is in the form of ?advice?.Based on the table above, it also can be concluded that there are five transitivity process used in this text. The major process used in this text is attributive process. In the second place is material, mental and verbal process with 17,7 %. Then, the last is 5,8% process of this text used behavioral process. In this text, there are also three major circumstance used those are location, extent and manner with frequency 25%. Then it?s continued by role and cause circumstance with 12,5%. In this text the system of Theme and Rheme provides important ways in which textual meanings at the clause level may be established. Theme-Rheme structure allows information to flow from one clause to another. The logical flow helps create cohesiveness of the text in the news. Theme is realized by position (initial). In the SFL an analysis of language, pattern of thematic choice are seen as realizing textual meanings, which in turn are the realization of mode dimensions of the context of situation, thus thematic choice realize meanings about the organization of the communicative event and the experiential and interpersonal distance.